2021
DOI: 10.33448/rsd-v10i12.20323
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Dysfunctions in COVID-19 Patients

Abstract: Coronavirus disease 2019 (COVID-19) is a respiratory viral infection caused by the novel coronavirus (SARS-CoV-2). Thus, it objected to comprehend the pathophysiology of COVID-19, as well as its clinical repercussions on hemodynamic alterations. This is an integrative literature review, such a method is able to select and include experimental and non-experimental studies, qualitative in nature, descriptive and exploratory in character. Initially, it started from the guiding question: "What hemodynamic dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
1
0
3
Order By: Relevance
“…Alguns autores comprovaram a terceira teoria, na qual os osteoclastos podem ser formados não apenas por células imaturas da linhagem monócito-macrófago, mas também por monócitos circulantes e macrófagos teciduais quando o ambiente fornecido é suficiente. Portanto, as duas últimas teorias constituem caminhos possíveis para o recrutamento de osteoclastos (fisiológica e patologicamente) (Ramalho, et al, 2000;Rezende, 2021).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Alguns autores comprovaram a terceira teoria, na qual os osteoclastos podem ser formados não apenas por células imaturas da linhagem monócito-macrófago, mas também por monócitos circulantes e macrófagos teciduais quando o ambiente fornecido é suficiente. Portanto, as duas últimas teorias constituem caminhos possíveis para o recrutamento de osteoclastos (fisiológica e patologicamente) (Ramalho, et al, 2000;Rezende, 2021).…”
Section: Resultsunclassified
“…É muito difícil coletar um grande número de osteoclastos de humanos para experimentos; no entanto, é relativamente fácil coletar grandes quantidades de MSP, que são precursores dos osteoclastos (Roodman, 2006;Rezende, 2021).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Coagulopathy can be one of the leading causes of death in COVID-19 patients. Some studies have also suggested that coagulation is associated with the severity of the COVID-19 symptoms (3). The results of published studies show that COVID-19 can also affect the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%